Tadeusz Różewicz pisze wiersze w roku 1946, czyli poeta modernistyczny wobec wojny - Pietrych, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The starting point for the remarks on the early oeuvre of Tadeusz Różewicz is the poem “Śmierć podchorążego” (“Death of a Cadet”) published in 1946 in the weekly Odrodzenie, and later included by the author in his famous volume Niepokój (1947) – which, however, was not reprinted later. “Śmierć podchorążego” shows fascination of young Różewicz with avant-garde poetry, especially the poetry of his contemporary master – Julian Przyboś. However, what is finally more interesting, the poem shows also—different than in the poem emblematic for Różewicz’s writings “Ocalony”—the attitude of the young poet to the subject of war. This different attitude is visible in his poetics as well as the interpretation of war experience included in this poem. Although, apart from the differences between “Śmierć podchorążego” and “Ocalony” there are also similarities. In both, Różewicz, as befits a modernist poet, tries to realize the postulate of the search for “new things”, which he formulated in his poetic manifesto published in April 1945.